한국의 반일(反日) 민족주의 연구: 담론의 변화와 특징 - 전재호; Jaeho Jeon (한국과 국제정치, 2019)
이 글은 해방 이후 70여 년간 반일 담론의 변화를 역사적으로 고찰했다. 한국의 반일감정에는 부러움, 질투와 분노, 증오가 복합적으로 응축되어 있고, 반일 담론은 그런 감정을 담아 표출하는 수로의 역할을 했다. 정치와 역사 부문에서 반일 담론은 냉전과 반공의 제약을 받았지만, 교육과 제도를 통해 그리고 과거사와 관련된 쟁점들이 계속 등장함으로써 21세기까지도 지속했다. 이에 비해 문화와 일상 영역에서의 반일 담론은 왜색일소 및 정부의 일본 문화와 상품 수입 금지에서 보이듯이 부정적인 의미를 담고 있었다. 그러나 그것들은 비공식적으로 유입되었고 1998년 대중문화가 개방되면서 이 영역에서의 반일 담론은 ‘사실상’ 소멸했다. 결국, 해방 후 70여 년간 정치, 역사 부문과 문화, 일상 영역에서 반일 담론은 상반된 방향으로 전개되었다. 이는 일본을 절대 악으로 간주하는 담론의 내포가 지속했던 데 비해 일본에 대한 반대를 의미하는 담론의 외연은 변화했음을 보여준다. This article examines the historical changes that have occurred in anti-Japanese discourse in Korea during more than 70 years, since the liberation of Korea from Japan in 1945. This discourse has played a key role in channeling the complex feelings of envy, jealousy, anger, and hatred that are condensed in the anti- Japanese sentiment in Korea. Although this discourse has been constricted by political and historical discourses surrounding the Cold War and anti-communism, it has continued into the 21st century through educational and other institutions, as well as because of the many issues related to unresolved past affairs. In the areas of culture and everyday life, anti-Japanese discourse historically appeared along with slogans such as a “Clean Sweep of Japanese Styles” which promoted the eradication of Japanese style. While, until 1998, the Korean government banned the importation of most Japanese culture and merchandise, both nevertheless flowed into Korea through unofficial channels. Then, since 1998, when the Korean government lifted this ban, anti-Japanese discourse in the fields of popular culture and commerce have practically died out. This article argues that anti-Japanese discourse has exhibited contrasting and bifurcating developments―between political and historical discourse, on the one hand, and culture and everyday life, on the other. As a result, while the connotations of anti-Japanese discourse which considers Japan to be an evil force have persisted, various denotations of anti-Japanese discourse have changed.